Attitudes Towards Personal Hygiene Among Elderly Male and Female Buddhists in Kuleshwar, Kathmandu - GC, Bishnu (JMC Research Journal, 2019)
This study presents the attitudes on personal hygiene practices among the male and female elderly Buddhists. The main objective of this study was to analyze and compare the attitude of male and female elderly Buddhists towards the personal hygiene practices. The study was completely based on descriptive research design as well as in quantitative nature. Total 70 respondents including 35 male and 35 female elderly Buddhists were selected purposively. In this study, the Likert's attitude scales with five alternatives separately for male and the female elders were used to collect the data and attitudes. It was found that most of the male and female elders had positive attitude towards the personal hygiene practices. It is concluded that there is no significant difference on male and female elders' attitudes towards the personal hygiene practices. Both have similar attitudes in terms of this perspectives.